Humidified high flow nasal cannula oxygen therapy in acute bronchiolitis - Ahmed, Parvez; Maqbool, Javid; Ashraf, Mohd (Indian Journal of Child Health, 2022)
Background: Bronchiolitis is a major cause of morbidity and leading cause of hospitalization, mostly in early childhood without coexisting illnesses. Traditionally dry oxygen is provided at 100% concentration via low flow nasal prongs. However, the latest studies have revealed that oxygen therapy via heated, humidified, high flow nasal cannula (HFNC) allows the delivery of high inspired gas flows which is better than the traditional one. Methods: All previously healthy children between 1 and 24 months of age with an established clinical diagnosis of moderate to severe bronchiolitis (clinical severity score ?4) were enrolled for study. The patients were divided into two groups: Patients in Group 1 received HFNC oxygen therapy (HFNC group) while those in Group 2 received conventional oxygen therapy (non-HFNC group). The patients were randomized in each arm by simple randomization. Outcome parameters measured were duration of hospital stay, duration of pediatric intensive care unit (PICU) stay, oxygen saturation (SPO2), respiratory rate, adverse event (respiratory failure), need for intermittent positive pressure ventilation or continuous positive airway pressure. Results: Out of 100 patients studied, 50 received HFNC oxygen and 50 received conventional oxygen. There was early and better improvement in SPO2 and respiratory rate (p<0.001), decreased length of hospital stay (p<0.001) and PICU stay (p<0.01) among the patients in HFNC group as compared to non-HFNC group. The most common adverse event during the hospital course was respiratory failure which was seen among 4 patients in non-HFNC group and none among HFNC group developed such complication. Conclusion: The use of HFNC oxygen therapy in infants hospitalized with acute bronchiolitis reduces PICU and hospital stay as well as the potential complications which will substantially reduce the hospital cost.